ANALISIS PENGARUH DIGITAL LITERACY DAN DIGITAL CAPABILITY TERHADAP CRITICAL THINKING MELALUI EMPLOYEE INNOVATION PADA PT PEGADAIAN AREA SURABAYA 2 - Anggraeni, Anggy Herny; Prasetyo, Indra (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2024)
This research was conducted at PT. Pegadaian Area Surabaya 2, this research aims to find out how the analysis of the influence of Digital Literacy and Digital Capability is on Critical Thinking through Employee Innovation. This research is Explanatory Research with a quantitative approach. Explanatory Research is research that explains the causal relationship between research variables through hypothesis testing. The respondents in this study were 62 employees spread across nine branches at PT. Pegadaian Area Surabaya 2. Data analysis technique using PLS (Partial Least Square) structural equation modeling analysis with SmartPLS 4.1.0.6. The results of this research show that existing Digital Literacy and Digital Capability abilities actually do not significantly influence the level of employee Critical Thinking. Digital Literacy and Digital Capability can have a significant direct effect on the ability to generate ideas through Employee Innovation in Surabaya Area 2. However, when Critical Thinking ability is connected to Employee Innovation as a mediating variable, both Digital Literacy and Digital Capability can have a significant effect indirectly. directly towards Critical Thinking. So it can be concluded that the higher the value of Digital Literacy and Digital Capability, the higher the Critical Thinking through Employee Innovation.